2010
DOI: 10.1099/jmm.0.020669-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lethal inhalational infection with Francisella tularensis in the common marmoset (Callithrix jacchus)

Abstract: The intracellular Gram-negative pathogen Francisella tularensis is the causative agent of tularaemia and is prevalent in many countries in the northern hemisphere. To determine whether the common marmoset (Callithrix jacchus) would be a suitable non-human primate model of inhalational tularaemia, a pathophysiology study was undertaken. Ten animals were challenged with ∼102 c.f.u. F. tularensis strain SCHU S4 (F. tularensis subsp. tularensis). To look for trends in the infection, pairs of animals were sacrifice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…This may, at least in part, be related to the higher dose used in the marmoset studies (2,3,12,15). In the current study, the time to death, activity, temperature profile, and bacterial load at postmortem in the nontreated animals were consistent with previously reported data (21). Clinical parameters were investigated in the current study and showed a statistically significant decrease in the platelet counts and an increase in the alkaline phosphatase levels, as well as notable changes in the levels of potassium, ALT, and glucose from the baseline.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This may, at least in part, be related to the higher dose used in the marmoset studies (2,3,12,15). In the current study, the time to death, activity, temperature profile, and bacterial load at postmortem in the nontreated animals were consistent with previously reported data (21). Clinical parameters were investigated in the current study and showed a statistically significant decrease in the platelet counts and an increase in the alkaline phosphatase levels, as well as notable changes in the levels of potassium, ALT, and glucose from the baseline.…”
Section: Discussionsupporting
confidence: 78%
“…However, in order to undertake the pivotal studies required for the licensure of any therapy, nonhuman primate models of infection are required. Previous work has demonstrated that the common marmoset (Callithrix jacchus) is susceptible to experimental inhalational tularemia and develops a lethal infection representative of human disease (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These are large, outbred animals, however, which limits the number of animals that can be studied, and they require large doses of prospective antibiotics, which limits the number of agents available to study. We therefore decided to explore the smaller New World primates and identified the common marmoset as a potential model for TB chemotherapy due to its small size (250 to 400 g as an adult), ease of husbandry, wide use in other disease models (10)(11)(12)(13)(14), and high incidence of dizygotic twinning (15). There was only a single case report of a zoonotic infection in the published literature involving a marmoset companion animal infected by a human in South Africa (16).…”
mentioning
confidence: 99%
“…68 Primates also develop skin ulcers and lymphadenopathy characteristic of human disease, whereas small animal models do not. 66 For these and other reasons, small animals are more suitable for proof-of-concept studies or to generate supportive data. Pivotal studies for approval of MCMs against tularemia under the Animal Rule will likely involve the use of NHPs.…”
Section: Existing Data For F Tularensismentioning
confidence: 99%